Strategies of Islamic Religious Education Teachers in Overcoming Learning Problems in Class V Students at SD IT Darul Chalidi NW Pringasela - Adi Faizun, Bustanul Arifin, Irwan, Juliani (Education Achievement: Journal of Science and Research, 2023)
Learning is an ongoing process and occurs continuously. Learning is very important, but in reality problems or obstacles often arise in the learning process. These obstacles come from within or from outside, there are still students who experience problems in learning, especially in terms of reading and understanding the Koran, control from parents and society which is not optimal is an obstacle that comes from outside. These learning obstacles will make it difficult for children to achieve maximum learning outcomes. Therefore, there must be a solution to overcome the obstacles that arise in children's learning. This research aims to 1) Find out the strategies of PAI teachers in SD IT NW Pringgasela, which is one of the educational institutions in the Pringgasela Main Village Area, Kec. Pringgasela. Regency. East Lombok. overcoming learning problems, 2) factors that cause learning problems in PAI subjects among Class V students at SD IT Darul Chalidi NW Pringgasela. In its implementation, the method used in data collection was Observation, Interview and Documentation methods, after it was deemed sufficient in data analysis, conclusions were drawn. In the learning process, Islamic Religious Education teachers have implemented learning strategies to the maximum. The importance of this research reflects the functional and managerial abilities of teachers in managing learning, turning the constraints into strengthening teacher capacity. Based on the research results, it can be concluded that teachers can overcome learning problems and carry out learning effectively through increasing capacity.